Water sensitive sample for determination of drops spectrum in spraying in coffee canephora - Vitória, Edney Leandro da; Campanharo, Alex (Coffee Science - ISSN 1984-3909, 2016)
The objective of this study was to determine the minimum number of water sensitive paper cards to be sampled in an experiment involving different spray nozzles and parts of conilon coffee. The experimental design was completely randomized in a factorial 2 x 2 x 2 (2 spray nozzles, 2 side spray, one in the direction of traversal of the spray and the other in the opposite direction; 2 Application heights in the plant, the lower half and the upper half), with 4 replicates. Each of the 24 experimental units consisted of 48 water sensitive paper cards. Four reproductive branches were selected, two branches belonging side of the sprayer to the pathway and the other two branches facing the opposite side of the spray traversal. They were established 24 water sensitive paper labels at the bottom and 24 on top of the plant, totaling 48 water sensitive paper. The average DMV, DMN, <100 and AR were significantly higher in the upper half of the plant on the same side of the spraying operation, regardless of the tip used. Using the tip JA-2 the lower side of the plant showed a mean VMD values, DMN, <100 AR and smaller than the upper half. The variances between DMV, DMN and RA were homogeneous. The number of labels per nine plant is indicated, since the greater the half-value widths (4.6 and 8%), the more homogeneous the number of labels per plant, independent of the variable, state and position of labels.